2020
DOI: 10.1109/access.2020.3014522
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Technology in Current Agricultural Systems: From Techniques to Applications

Abstract: Increasingly, blockchain technology is attracting significant attentions in various agricultural applications. These applications could satisfy the diverse needs in the ecosystem of agricultural products, e.g., increasing transparency of food safety and IoT based food quality control, provenance traceability, improvement of contract exchanges, and transactions efficiency. As multiple untrusted parties, including small-scale farmers, food processors, logistic companies, distributors and retailers, are involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(114 citation statements)
references
References 88 publications
0
110
0
4
Order By: Relevance
“…The search fields were defined differently in different databases, as described in Table 1. After each selection stage, the selected papers were counted and documented in a common spreadsheet during the selection process, adapted from [24], presented in Figure 2. Out of 147 originally found papers, 69 publications were subsequently shortlisted for detailed analysis, among which 25 were conference papers, 40 were journal publications, and 4 book sections, which resulted in a selection rate of 46.94%.…”
Section: Search In Databasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The search fields were defined differently in different databases, as described in Table 1. After each selection stage, the selected papers were counted and documented in a common spreadsheet during the selection process, adapted from [24], presented in Figure 2. Out of 147 originally found papers, 69 publications were subsequently shortlisted for detailed analysis, among which 25 were conference papers, 40 were journal publications, and 4 book sections, which resulted in a selection rate of 46.94%.…”
Section: Search In Databasesmentioning
confidence: 99%
“…There have been initiatives addressing current barriers and applications of blockchain implementation in supply chains [7,8,10], addressing benefits and challenges of adoption in FSCs [3,7,22], with content-based analysis [13] and suggestions for future research directions [10] for improved sustainability of FSCs [13,17,22]. In recent publications, the challenges of scalability, security, and privacy of DLT and IoT solutions were highlighted as some of the most critical in ongoing research [10,[22][23][24][25][26]. This systematic literature review (SLR) paper provides content-based detailed analysis and systematic review of papers, addressing technical details of DLT and IoT implementation in FSCs with the following contributions and objectives:…”
Section: Introductionmentioning
confidence: 99%
“…Their system implements a response mechanism for various events for an improved, validated, and guaranteed transaction. In a survey paper, Lin et al (2020) showed how blockchain and IoT-based systems contribute to food safety, food security, food quality monitoring, and control to support small-scale farmers. Legacy information is vital for making decisions about a product as food can be categorized and sometimes prohibited for several reasons.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Blockchain for 5G-enabled IoT for industrial automation: A systematic review, solutions, and challenges [14] 2020 NA Blockchain Technology in Current Agricultural Systems: From Techniques to Applications [33] 2020 NA Blockchain and supply chain sustainability [34] 2020 79…”
Section: Benefits and Challenges: A Review Of Reviewsmentioning
confidence: 99%